The politics of moralizing - Bennett, Jane, 1957-; Shapiro, Michael J. (Routledge, 2002)
The Politics of Moralizing issues a stern warning about the risks of speaking, writing, and thinking in a manner too confident about one's own judgments and asks, ""Can a clear line be drawn between dogmatism and simple certainty and indignation?"" Bennett and Shapiro enter the debate by questioning what has become a popular, even pervasive, cultural narrative told by both the left and the right: the story of the West's moral decline, degeneration, or confusion. Contributors explore the dynamics and dilemmas of moralizing by advocates of patriotism, environmental protection, and wom.